ANALISIS YANG MEMPENGARUHI NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020) - Mohklas, Mohklas; Nurcahyati, Sinta Dea (Jurnal Akuntansi dan Bisnis, 2022)
This study aims to analyze the effect of Leverage, Return On Assets (ROA), and Institutional Ownership on Firm Value. Multiple linear regression data analysis methods, and hypothesis testing. The population in this study is companies whose shares remain incorporated in the LQ-45 index and must always be actively traded every day during the 2017-2020 period. The sample in this study used purporsive sampling method, in order to obtain a sample of 112 companies. Research result; Partially Leverage and Institutional Ownership have no significant effect on firm value, while Return on Assets (ROA) has a significant effect on firm value.Keywords: Leverage, Return On Asset (ROA), Institutional Ownership, Value Company